On the use of the C map in Patterson deconvolution procedures. (20th December 2012) - Caliandro, Rocco; Carrozzini, Benedetta; Cascarano, Giovanni Luca; Comunale, Giuliana; Giacovazzo, Carmelo
<x xml:space="preserve">Abstract</x> The cross‐correlation function between the target and a model electron density, denoted as the C map, has been crystallographically characterized. In particular, a study of its interatomic vectors and of their relation with the Patterson vectors has been undertaken. Since the C map is not available during the phasing process, the C′ map, its centric modification, is considered. It may be computed at any stage of the phasing process and shows properties that are very useful for the crystal structure determination process. It has been combined with the implication transformation method and with vector‐superposition techniques for performing the Patterson deconvolution and obtaining an initial model for dual‐space recycling. While Patterson methods are traditionally considered to be more efficient for structures containing heavy atoms, the C map extends their potential to light‐atom structures (i.e. containing atoms not heavier than O).